PENGARUH HARGA JUAL PRODUK JAGUNG GORENG TERHADAP PENDAPATAN PADA UMKM HM MANDIRI DI KELURAHAN FATUBESI KOTA KUPANG - Corinitha Imelda Tali Laiskodat; Stefanus Reinati; Marselinda A. Hege (P3M Politeknik Negeri Ambon, 2025)
This study aims to examine the effect of selling price and production quantity on the income of HM Mandiri Micro, Small, and Medium Enterprises (MSMEs) in Fatubesi Subdistrict, Kupang City. The data used include production quantity and income from fried corn products during the period 2022–2024. The research method applied is simple linear regression analysis and correlation test to determine the relationship and influence between variables.The results indicate that production quantity and income of HM Mandiri MSMEs fluctuated each year. Regression analysis shows a positive but very weak relationship between production quantity and income. The correlation coefficient (r = 0.072) and determination coefficient (r² = 0.0051) indicate that production quantity contributes very little to income, while the remaining variation is influenced by other factors. The t-test results also show that the effect of production quantity on income is not significant.Based on these findings, it can be concluded that increasing production quantity does not automatically increase the income of HM Mandiri MSMEs. Therefore, income improvement strategies should focus on other factors such as marketing, product quality, production cost efficiency, and product innovation.Keywords: production quantity, selling price, income, fried corn.